SISTEM MONITORING DAN KONTROL KUALITAS AIR PADA AKUARIUM - Muhtadil Haq; Denny Irawan (Universitas Muhammadiyah Gresik, 2024)
Aquarium, which is a glass made in such a way that it functions as an artificial habitat for goldfish. The aquarium will be made as comfortable as possible for the fish to live in so that they do not easily experience stress and die. The problems often experienced by aquarium owners, many owners still do not pay attention to the conditions in the aquarium environment, namely water pH, temperature, turbidity, salt levels. So this aquarium was created using a water PH sensor, temperature sensor, turbidity sensor and salinity sensor to take water quality readings and then process them in ESP32 using the results of these sensor readings which will be displayed on the LCD screen and recorded in Google SPedsheed. ESP32 will give orders to the pump to dissolve the solution that has been set to neutralize the water pH of 6.5-7.5 if the water is in alkaline/acidic conditions. When the temperature sensor reaches 25°C the heater will turn on, but when the temperature is above 30°C there is no action. The pump will also turn on to regulate water turbidity and normal water salt levels, and will turn off if the water is in good turbidity conditions, namely below 10 NTU and good salt levels, namely 4 ppt. This system can monitor and control water quality in real time and is able to provide notifications when water quality exceeds a predetermined standard value. By making this tool, the water quality parameters are recorded well, so that the fish grow well and do not experience stress or death.